Construction and cryopreservation of an artificial ovary in cancer patients as an element of cancer therapy and a promising approach to fertility restoration. (8th August 2022) - Chen, Jing; Todorov, Plamen; Isachenko, Evgenia; Rahimi, Gohar; Mallmann, Peter; Isachenko, Vladimir
Abstract: The proportion of cancer patients that survive is increasing because of improvements in cancer therapy. However, some cancer treatments, such as chemo- and radio-therapies, can cause considerable damage to reproductive function. The issue of fertility is paramount for women of childbearing age once they are cured from cancer. For those patients with prepubertal or haematogenous cancer, the possibilities of conventional fertility treatments, such as oocyte or embryo cryopreservation and transplantation, are limited. Moreover, ovarian tissue cryopreservation as an alternative to fertility preservation has limitations, with a risk of re-implanting malignant cells in patients who have recovered from potentially fatal malignant disease. One possible way to restore fertility in these patients is to mimic artificially the function of the natural organ, the ovary, by grafting isolated follicles embedded in a biological scaffold to their native environment. Construction and cryopreservation of an artificial ovary might offer a safer alternative option to restore fertility for those who cannot benefit from traditional fertility preservation techniques. This review considers the protocols for constructing an artificial ovary, summarises advances in the field with potential clinical application, and discusses future trends for cryopreservation of these artificial constructions.